Implementasi Manajemen Keuangan Sekolah Dan Implikasi Terhadap Kualitas Pendidikan Di Yayasan Perguruan Al-Islam Surakarta - Halimah, Miftah Nurul; , Tri Nur Wahyudi, S.Pd, MM (2017)
This study aims to find out how the planning and implementation of financial management in improving the quality of education and the influence of financial management management on the quality of education. This study uses a combination of research methods with mixed balanced research design QUALITATIVE and quantitative (Concurrent embedded). The results of this study showed that financial planning in MA Al-Islam Jamsaren Surakarta starts with the formation of Madrasah Work Plan and Budget (RKAM) formulated by principals and their staffs for activities during the school year. With the allocation of funds amounting to 34.94% budgeted for the development of quality so that in the procurement of funds for the quality of education has been highly considered. In the execution itself MA Al-Islam Jamsaren always refer to the national standard of education is positively correlated to the quality of education. Based on the results of quantitative data as the data amplifier using the linear regression equation is expressed by the equation Y = 19.825 + 0,486X which means that if the implementation of financial management is positively correlated with the quality of education, based on t test results obtained thitung 4.283> 1.833 ttabel which means that there is significant influence implementation Financial management on the quality of education at MA Al-Islam Jamsaren Surakarta.